Evaluasi Penggunaan Antibiotik pada Pasien Rawat Jalan di Puskesmas Pekan Heran dengan Metode Anatomical Theraupetic Chemical/ Defined Daily Dose and Drug Utilization Drug - Ayu Dwi Utami; Lila Wahyuni; Futri Handayani; Jhoti Sumitra; Sri Sukria; Nova Marnovy (JURNAL FARMASI DAN MAKANAN, 2024)
Antibiotics are one of the highest used drugs in the world. Relatively high use of antibiotics can increase the risk of antibiotic resistance. Based on several studies in Indonesia, the use of antibiotics in several Public health center shows the high use of antibiotics. This study aims to find out how antibiotics are used at the Pekan Heran health center in 2019-2022 using the ATC/DDD method and to see changes in the profile of antibiotic use based on the 90% DU profile which is calculated in units of DDD/1000 KPRJ. In this study, there were 8 drugs used at Pekan Heran Public Health Center, namelyamoxicillin, clindamyycin, erythromycin, cefixime, contrimoxazol, metronidazole, chloramphanicol and cefadroxil. Data collection was obtained from the Pekan Heran Public health center. The data processing uses the ATC / DDD method which is processed using Microsoft Excel. The results show that the quantity of antibiotic use has always fluctuating during the 2019-2022 period. The highest use of antibiotic drugs was in 2019 amounting to 708,233 DDD / 1000 KPRJ, and the smallest use was in 2021 amounting to 1,157 DDD / 1000 KPRJ. The profile of the use of antibiotic drugs at the Pekan Heran Public health centerfor the period 2019-2022 was based on DU90%, namely amoxicillin, erythromycin and metronidazole. Amoxicillin is the highest drug used with a percentage in 2019, namely 48,006%, in 2020 amounting to 58,054%, in 2021 it was 27,072%, in 2022 it was equal to 28,437%